The effect of nicotine withdrawal on hygiene and oral health - Markowska-Dyner, Agnieszka (Journal of Education, Health and Sport, 2018)
Introduction and purpose of the work. There are many reports in the literature about the negative impact of smoking on oral hygiene and health. Periodontal disease, which most often occurs in smokers, is also a source of many other ailments that determine the health of a person. The nicotine withdrawal is observed in smokers in relation to hygiene and oral health. The process of nicotine withdrawal is long-lasting but brings tangible results, both in the aspect of hygiene and oral health. The aim of this work is to present the effects of nicotine withdrawal in individual stages of its process. State of knowledge. According to numerous reports, smoking is one of the most important factors threatening the health of people in highly developed countries. It is a medical, social, moral and economic problem. Epidemiological data indicate that in Poland, 9 million people smoke cigarettes. In the world, active tobacco smokers are over 1 billion. It turns out that smoking kills as many as 5.8 million people around the world. Estimates indicate that this number could reach up to 8 million in 2030 [1, 2]. The Ministry of Health in Poland calculated, that as a result of the tobacco addiction, up to 67,000 Poles die each year, e.g. only lung cancer caused by smoking kills about 20,000 people a year[3].In the light of the study carried out by TNS Polska for the Chief Sanitary Inspectorate, one in four Poles after the age of 15 is a smoker, and the number of smokers is decreasing every year. The epidemiological studies have demonstrated the significant effect of smoking on the oral cavity and the development of periodontal disease. At the same time, the literature of the subject have indicated the measurable effects of nicotine withdrawal - reducing the negative effects on oral health. In the short-term assessment, the negative effects reduction is rather more visible for society and the former smoker - namely the lack of unpleasant smell from the mouth, as well as the smell of clothes and hair, or the improvement of taste and smell. In the case of prolonged nicotine abstinence, there is a reduction in the risk of periodontal disease and mucous membrane diseases. Long-term discontinuation of smoking may cause significant improvement in periodontium and contribute to the regression of pathological lesions on the oral mucosa, as well as the lack of further progression of diseases resulting from smoking addiction. Summary. The literature on the subject as well as the results of analyzes carried out in dental offices confirm that there is a measurable benefit to oral health through the use of nicotine withdrawal. Each stage characterized by a period of abstinence has benefits that cause the negative effects of smoking to regress. It is obvious that the patient’s commitment and compliance with the dentist’s instructions regarding the pharmacological support of the entire process, but also all preventive measures is very important.